Diagnostic Accuracy of Contrast-Enhanced MRI for Detecting the Malignant Breast Lesions - Mahjabeen Yaseen, Shagufta Naqvi, Amna Saleem, Rida Nasreen, Rida Imran, Aysha Mahmood (Journal of Rawalpindi Medical College, 2021)
Objectives: To determine the accuracy of contrast-enhanced MRI in the diagnosis and detection of breast lesions and their malignant potential by taking the gold standard of histopathology. Materials and Methods: This study was conducted at the Department of Diagnostic Radiology, Pakistan Institute of Medical Sciences (P.I.M.S.) Islamabad. It was undertaken in collaboration with the Department of General Surgery P.I.M.S, Department of Pathology P.I.M.S Islamabad, and HIT Hospital Taxila. The study design was a cross-sectional (Validation) study and the duration of the study was 6 months (from 01-Oct-2016 to 31-Mar-2017). Results: Sample size was calculated by using sensitivity and specificity calculator taking sensitivity 94%1 with a precision of 6%, specificity 85%1 with a precision of 10%, prevalence is 45.9%2, and confidence interval of 95% it comes out to be 92%. Sample collection was made by the technique of Consecutive non-probability sampling. Conclusion: Breast MRI imaging is a modern evolving modality. A gradual increase in diagnostic specificity is achieved with improved software and techniques. More such studies would help develop confidence in this advanced imaging modality for improving patient management and avoiding unnecessary biopsies.